PERFORMANCE OF GHUNGROO PIGS UNDER INTENSIVE HOUSING SYSTEM (Indian Journal of Animal Production and Management, 2015)
The study was carried out on 24 Ghungroo sows kept under controlled breeding programme at instructional farm of College of Veterinary Sciences, Central Agricultural University, Aizawl, Mizoram to observe the performances of piglets and sows. The study revealed that the litter size was highest in second parity and subsequently declined till fourth parity. The body weight was also lowest in the fourth parity. ADG was highest in the fourth week and lowest in the first week. The weekly body weight showed a progressive increase in the body weight. The overall mortality was 29.6 % and it was highest in 1st to 2nd week.
Keywords: Ghungroo; Performance; Intesive housing